When misinterpretation leads to sexism: perspectives on gender disparity in Brazilian Herpetology - Maria Diele Viegas, Luisa; Gabriela dos Santos Araújo, Olívia; Von Muller Berneck, Bianca; Aguirre Brasileiro, Cinthia; Silva Brito, Elizângela; Brunes, Tuliana O.; Helena Condez, Thais; Cagliari Costa, Laisla; Dias Silva, Fernanda; Fenker, Jéssica; Maria Xavier Freire, Eliza; Iop, Samanta; et al. (Herpetologia Brasileira, 2026)
In a recent article published in Nature Communications, AlShebli et al. (2020) analyzed the mentor-protégé relationship in scientific collaborations. Specifically, they examined the impact of gender on scientific careers and concluded that women scientists should rely on male guidance for a successful career and higher publication impact. Here, we respond to these authors criticizing the superficial interpretation of their findings and the likely disastrous impact for the fight for gender equity in academia, focusing on the field of Brazilian Herpetology. Our goal is to highlight women’s role as mentors in Herpetology, contextualizing the gender gap in our field with the literature in gender studies.